Characterisation of Biosurfactant Produced by Bacteria from Environmental Isolates - Ong, Albert Sze Yung (2017)
Biosurfactants that are widely utilised in various fields such as environmental bioremediation and cosmetic industry have been identified to exhibit antimicrobial and anti-adhension properties in recent years. Studies show that biosurfactants can inhibit bacterial adhesion through bio-conditioning of a surface by changing the surface’s hydrophobicity or by interacting directly with the bacterial cells to modify their surface properties. In this study, 10 environmental bacterial isolates were subjected to preliminary screening assays consisting of blood agar haemolysis test and oil spreading assay to screen for isolates capable of producing biosurfactants. Bacterial isolates 9 and 10 were selected as the biosurfactant producers because they yielded larger diameter in the oil spreading assay compared to other bacterial isolates (p<0.05). Both biosurfactants from bacterial isolates 9 and 10 showed emulsification capacity similar to that of the control, Triton X-100 in emulsifying toluene and hexadecane (p>0.05). Based on the Bacterial Adhension to Hydrocarbon (BATH) assay, bacterial cells from the bacterial isolates 9 and 10 inhibited adhesion of P. aeruginosa and S. aureus bacterial cells at a concentration of 0.1 g/mL (p>0.05). biosurfactant from bacterial isolate 10 showed significant antimicrobial property against both P. aeruginosa and S. aureus while biosurfactant originated from bacterial isolate 9 only showed significant antimicrobial property against P. aeruginosa. Overall result suggest that both biosurfactants from the bacterial isolates 9 and 10 exhibited potential values as biofilm-forming inhibitor and antimicrobial agent to be used in the medical field.